2021
DOI: 10.21608/ejentas.2021.76357.1369
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Acute Invasive Fungal Rhinosinusitis: A Comparative Study

Abstract: Background: Acute invasive fungal rhinosinusitis (AIFR) is a potentially fatal infection that usually complicates immunosuppressive status like uncontrolled or newly discovered diabetes mellitus, during the coronavirus disease (COVID19) pandemic, worsening of underlying diabetes and newly discovered cases have been observed. Aim: To highlight the impact of COVID-19 on emerging cases of AIFRS comparing this with AIFR before COVID-19 pandemic. Methods: This is a retrospective comparative study between AIFR patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Chronic kidneys and liver diseases, multiple organ dysfunction syndrome are also significant risk factors for bacterial-fungal chronic rhinosinusitis development [43]. In our study, chronic hepatitis was detected in 1 case (9.1%), chronic glomerulonephritis -in 1 case (9.1%), chronic pyelonephritis -in 1 case (9.1%).…”
Section: Discussionsupporting
confidence: 47%
“…Chronic kidneys and liver diseases, multiple organ dysfunction syndrome are also significant risk factors for bacterial-fungal chronic rhinosinusitis development [43]. In our study, chronic hepatitis was detected in 1 case (9.1%), chronic glomerulonephritis -in 1 case (9.1%), chronic pyelonephritis -in 1 case (9.1%).…”
Section: Discussionsupporting
confidence: 47%
“…Ebeid et al [ 58 ] reported a dramatic increase in the rate of incidence of AIFR in patients with recent COVID-19 infection in comparison with pre-COVID-19 pandemic numbers. For 6-month period between July and December 2020, Tanta university hospitals (Egypt) admitted 28 AIFR patients.…”
Section: Discussionmentioning
confidence: 99%
“…The exact pathophysiological mechanisms of this co-infection are unknown. It has been suggested that the incidence of IFRS is higher in post-COVID-19 patients than in non-COVID-19 patients [3,4], notably, in immunocompetent patients. Research on SARS-CoV and SARS-CoV-2 showed remarkable similarities in their mechanisms, both increasing the incidence of fungal invasion.…”
Section: Discussionmentioning
confidence: 99%